Organic materials for active layers in transistors: Study of the electrical stability properties - Gomes, Henrique L. (2015)
Field effect transistors based on several conjugated organic materials were fabricated and assesed in terms of electrical stability. The device characteristics were studied using steady state measurements as well as techniques for addressing trap states. Temperature-dependent measurements show clear evidence for an electrical instability occurring above 200 K that is caused by an electronic trapping process. It is suggested that the trapping sites are created by a change in the organic conjugated chain, a process similar to a phase transition.